Case report: Death caused by 1, 3-dichloropropene, a novel fumigant used in China - Zhiqiang Zhou; Zhiqiang Zhou; Lanlan Guo; Lanlan Guo; Zixin Wen; Zixin Wen; Ping Dai; Tongyue Zhang; Wenjun Wang; Xiangdong Jian; Xiangdong Jian (Frontiers Media S.A., 2023)
As an efficient and broad-spectrum soil fumigant, 1, 3-dichloropropene is widely used in the control of nematodes, soil pests, and plant pathogens. However, as a volatile chlorine-containing organic compound, 1, 3-dichloropropene is harmful to human health, although no deaths caused by inhalation of 1, 3-dichloropropene have been reported. This article describes the case of a 50-year-old man who died of acute renal failure and brain edema after inhaling 1, 3-dichloropropene at work. This case demonstrates that 1, 3-dichloropropene can be absorbed through the respiratory tract and that exposure to 1, 3-dichloropropene in a confined environment without any protective measures can cause death in humans.